136k views
5 votes
1. Let f(x) = 7x2 – 5x + 3 and g(x) = 2x2 + 4x – 6.

Part A: Find f(x) + g(x)
Part B: Find f(x) – g(x)
Part C: Find g(x) – f(x)

1 Answer

4 votes

Answer:

f(x) + g(x) =
9x^(2) - x - 3

f(x) - g(x) =
5x^(2) - 9x + 9

g(x) - f(x) =
-5x^(2) + 9x - 9

Explanation:


f(x) = 7x^(2) - 5x + 3\ and\ g(x) = 2x^(2) + 4x - 6

Case 1:

f(x) + g(x)

=
7x^(2) - 5x + 3 + (2x^(2) + 4x - 6)

=
7x^(2) - 5x + 3 + (2x^(2) + 4x - 6)

=
9x^(2) - x - 3

Case 2:

f(x) - g(x)

=
7x^(2) - 5x + 3 - (2x^(2) + 4x - 6)

=
7x^(2) - 5x + 3 - 2x^(2) - 4x + 6

=
5x^(2) - 9x + 9

Case3:

g(x) - f(x)

=
2x^(2) + 4x - 6 - (7x^(2) - 5x + 3)

=
2x^(2) + 4x - 6 - 7x^(2) + 5x - 3

=
-5x^(2) + 9x - 9

User Carel
by
5.9k points